Penguatan Dewan Perwakilan Daerah Terkait Fungsi Legislasi dalam Perspektif Demokrasi Deliberatif - Dharmapala, Ario; Dewi, Sri Anggraini Kusuma; Iswahyudi, Gesang (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The Regional Representative Council is one of the people's representative institutions in Indonesia. The Regional Representative Council is a regional representative who is elected through general elections. However, in the Indonesian constitution, the 1945 Constitution of the Republic of Indonesia, the position of the Regional Representatives Council is weaker than the House of Representatives. This study aims to emphasize the urgency as well as future arrangements for strengthening the functions of the Regional Representatives Council. The legal issue in this study is the legal vacuum in regulating the legislative functions of the Regional Representatives Council in the perspective of deliberative democracy. This research is a normative legal research using a conceptual approach and legislation. The legal materials used are primary legal materials such as the Constitutions of Indonesia, the Netherlands, America, and Germany. Secondary legal materials include all results of studies and research on people's representative institutions, and non-legal materials are legal dictionaries. The results of the study confirm that the urgency of strengthening the legislative function of the Regional Representatives Council is needed, especially in relation to the theory of deliberative democracy. In addition, in the future it is necessary to amend the constitution to strengthen the position of the RegionalRepresentative Council.